The critical thinking research trend in Indonesia's language education journals - Zikrullah, Muhammad; Azhari, Azhari (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2024)
In the 21st century, education aims to develop research writing skills for critical thinking, emphasizing creative, collaborative, and communicative thinking skills in all programs. The study aims to gather information about a variety of studies discussing critical thinking skills in Indonesia using content analysis in many scientific language education journals published in Indonesia. This study used content analysis. Data were obtained by collecting papers that had been published in language education publications across Indonesia from 2016 to 2023, reading carefully, classifying based on the research instrument, and data was analyzed using classical content analysis technique. The results of this study, there have been more publications over the last three years that highlight critical thinking abilities. The majority of the research design used in those papers was quantitative. Furthermore, the most targeted subjects and materials were